ПУБЛИЦИСТИКАЛЫҚ ТЕКСТ СТИЛИСТИКАСЫН ҮЙРЕНИЎДИҢ ТЕОРИЯЛЫҚ тийкарлары - Пирниязова, А.К.; Каллибекова, Г.П. (FAN va JAMIYAT, 2025)
The article provides an overview of the literature studying the stylistics of journalistic texts. In the field of Karakalpak journalism, this topic has not been studied. The relevance of this topic is revealed.